Diversidad alfa de las especies forestales del bosque de terraza baja de la comunidad nativa Nuevo Iquitos, distrito de Capelo. Loreto. 2023 - Paiva Diaz, Leonard Elí (2025)
In the low terrace forest of the native community Nuevo Iquitos, Capelo district, Loreto, alpha diversity was assessed by inventorying all trees with a minimum DBH of 10 cm in two randomly located 1 ha plots. The Margalef index reflected a high species richness, with values of 6.02 in plot 1 and 6.0 in plot 2. In plot 1, Inga bourgonii stood out with a value of 1.335, while in plot 2 Macrolobium ocaciifolium and Myroxylon balsamum (1.3328) stood out. Simpson's index showed low dominance in both plots, with 0.1024 in plot 1 and 0.0380 in plot 2, indicating a balanced distribution among species. Inga bourgonii was key in plot 1 (0.0032), while Macrolobium ocaciifolium (0.0040) and Myroxylon balsamum (0.0036) stood out in plot 2. The Shannon-Wiener index reached 3.555 in plot 1, indicating moderately high diversity, and 2.779 in plot 2, reflecting moderate diversity. These results suggest that alpha diversity varies among plots, partially supporting the hypothesis. Differences in richness and diversity indices appear to be influenced by micro environmental factors and the spatial distribution of species.